Cilengitide affects tumor compartment, vascularization and microenvironment in experimental bone metastases as shown by longitudinal 18F-FDG PET and gene expression analysis - Bretschi, Maren; Cheng, Caixia; Witt, Hendrik; Dimitrakopoulou-Strauss, Antonia; Strauss, Ludwig G.; Semmler, Wolfhard; Bäuerle, Tobias (Journal of cancer research and clinical oncology, 2013)
Aim of this study was to investigate the specific treatment effects of inhibiting αvβ3/αvβ5 integrins by cilengitide in an animal model of breast cancer bone metastases using dynamic 18F-FDG PET and gene expression analysis.